The Influence Of Hinduism Toward Islam Bani: Study Of Religious Thought Of Muslim Champa, Viet Nam - Ismardi, Zulkifli, Kamiruddin; Afrizal Ahmad (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2018)
This article would like to traceabout: when is the emergence of Bani Islam, what is the teachings of Islam Bani,what is the influence of Hinduism toward Muslim worship of Bani Vietnamese, andwhat are the Vietnamese Muslim businesses in purifying/renewing their teachings. This article was conducted in NinhThuan Province, Vietnam in 2017. The subject of the study were the figures of the Champa Muslim community (Bani and Cham Islam), then the worshipers of the two groups above. The object of this research was Hindu effect on Bani Islam.The population in this research were the Bani religious figures and Cham Islam/Sunni whose numbers could not be identified completely because they were spread in various regions. The analysis that the author used in this study was a Qualitative Descriptive analysis. This article concludes thatin Vietnam there are two Islamic groups namely Cham Islam and Early Cham (Cham Bani). The way to worship the Cham Bani group was influenced by Hinduism, which has become a tradition of Vietnamese society before the arrival of Islam. This happened due to the unfinished Islamization process.Cham Bani's way of worship is still going on nowadays, even though there have been purification efforts from various parties to improve the way they worship.